2016
DOI: 10.20961/jiep.v14i1.2012
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pengembangan Usahatani Kedelai Di Kabupaten Grobogan Dengan Pendekatan Analysis Hierarchy Process (Ahp)

Abstract: <p>Soybean is one of the agricultural commodity Grobogan. Soybean commodity is widely cultivated by farmers because the topography is consistent with the characteristics of the soil in Grobogan. In 2010 soybean production Grobogan is most widely in Central Java. However, Indonesia is still dependent on imported soybeans, especially in times of shortages of soybeans. This is partly also due to soybean production in soybean-producing region is very volatile while soybean demand in the market tends to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The questionnaire is prepared based on the Saaty scale with weights of values 1 to 9. The weight value 1 describes 'equal importance', this means that the attribute value is the same scale, the weight value is 1, while the weight value 9 describes the case of the attribute being 'absolute importance' compared to everything else (Sudantoko, 2010). A value of 1 means that both criteria (elements) are equally important.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire is prepared based on the Saaty scale with weights of values 1 to 9. The weight value 1 describes 'equal importance', this means that the attribute value is the same scale, the weight value is 1, while the weight value 9 describes the case of the attribute being 'absolute importance' compared to everything else (Sudantoko, 2010). A value of 1 means that both criteria (elements) are equally important.…”
Section: Methodsmentioning
confidence: 99%
“…The depiction of fauna takes animals that have proximity to community life activities such as chickens, birds, and butterflies. Compositions from animals and plants are applied to typical Banyumasan motifs, among others: Gowokan, Lumbon, Pring Sedhapur, Angrem Baboon, Manggar, and Jaheyan (Sudantoko, 2010). The motifs in Banyumasan batik represent the life of the people who make it where geographically Banyumasan is an area that is classified as a mixture of coastal culture and inland culture (Utomo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The age of the respondents showed that the overall productive age of the respondent farmers was 15-64 years. The younger the age, the farmers tend to International Journal of Agricultural Social Economics and Rural Development (Ijaserd) 2023: 3(2):51-58 eISSN: 2774-9126 have a more muscular physique and dynamic in managing their farming, so they can work stronger than farmers who are generally old (Setiawan & Fafurida, 2016). This gives the idea that respondent farmers still have the physical strength to work to process soybean farming, so with these conditions, they are expected to carry out activities optimally and increase their income.…”
Section: Identity Of Respondentsmentioning
confidence: 99%
“…This great opportunity is certainly supported by the segmentation of consumers who are Muslims. There are approximately 1.57 billion Muslims in the world living in more than 100 countries (Setiawan & Hasanah, 2023). The Global Muslim Travel Index 2022 report by Mastercard-CrescentRating states that in 2022 the total Muslim population in the world will reach 2 billion people (Santika, 2023).…”
Section: Introductionmentioning
confidence: 99%